Influence of weed management and parasitoids of lepidopterous pest in intercropped sorghum and maize in southern Honduras - Cordero, R.J.=700 1 Pitre, H.N.; Cave, R.D.
(Es, En)
Ilus., 21 ref.
Keywords: SPODOPTERA FRUGIPERDA; LEPIDOPTERA; NOCTUIDAE; PARASITISMO; MALEZAS; INSECTA; PLAGAS; HONDURAS